PENGARUH SUBSITUSI TEPUNG SAGU TERHADAP KUALITAS KULIT PIE - Tobing, Lukman Muhammad; Yulastri, Asmar; Gusnita, Wiwik (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was motivated by the utilization of sago flour which is used in diversification of food processing, while sago flour can be one alternative to replace some of flour as the main ingredient of pie skin. This study aims to analyze the influence of substitution of sago flour as much as 25%, 50% and 75% to the quality of pie skin in terms of shape, color, aroma, texture and taste. This type of research is a pure experiment using a completely randomized design method. The data used were primary data sourced from 30 semi-trained panelists by proposing the organoleptic test format. Analyze data using ANAVA, if FCcount> FTable then proceed with Duncan test. The result of this research is significant influence from the use of sago flour to the quality of pie skin with the use of sago flour as much as 75% produce the best quality pie skin, including brownish yellow color, to the quality of sago aroma and for the taste of sago. Keywords: Substitution, Sago Flour, Skin pie, Quality.